SOLE 2021/26th Annual Meetings (Journal of Labor Economics, 2020)
Previous articleNext article FreeSOLE 2021/26th Annual Meetings Call for PapersPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreThe Society of Labor Economists will hold the 26th Annual Meetings on May 14–15, 2021, at the Sonesta Philadelphia, 1800 Market Street, Philadelphia, Pennsylvania 19103.Complete papers should be submitted for both full and poster sessions. Only one submission per person is permitted. Keep checking the website at https://sole-jole.org for a link to the submission portal.The deadline for submission is October 31, 2020.Robert Moffitt, PresidentKevin Lang, President-ElectThomas Lemiux, Vice President Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 38, Number 3July 2020 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/709392 © 2020 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.